Sistema para el compartimiento de archivos usando la norma ISO 27000 para digitalizar y centralizar la información administrativa y académica del colegio Dr. Trajano Naranjo Iturralde - Chisaguano Mullo, Klever Patricio (2016)
The research project was to carry out the implementation of a system for the sharing of files using the ISO 27000 to digitize and centralize the academic and administrative information of the Dr. Trajano Naranjo Iturralde School, with the purpose to facilitate the information and provide with greater agility and quickness. Effective tools for the implementation of the system were used as C Sharp a feasible system programming, easy to handle with a striking structure for both the developer and the user.